Analysis of Digital Marketing Live, Promotion, Short Video Strategies on Gen Z Skincare Purchasing Decisions - Muhamad Novreysa; Aura Puspaningrum; Erna Apriani; Indra Permana; Abdul Latif (JMET: Journal of Management Entrepreneurship and Tourism, 2025)
In today's ever-evolving digital age, social media platforms like TikTok have become a powerful tool to influence purchasing decisions, especially among Gen Z. TikTok provides interactive features such as live streaming, promotions, and short videos, effectively capturing the audience's attention with engaging and accessible content. Skincare businesses utilize these features to increase brand awareness, boost engagement, and motivate consumers to purchase. This study aims to determine the significant influence between live streaming, short videos, and marketing on consumer purchasing decisions on the TikTok application. The method used is a quantitative method with a sample size of 100 respondents through a questionnaire survey, and this data was analyzed using the SmartPLS application. The results showed that all variables have an Average Variance Extracted (AVE) value above 0.50, which means the validity is quite good. In addition, Cronbach's Alpha value of more than 0.70 indicates that all variables are highly reliable. R-Square analysis shows that 78.6% of purchasing decisions are influenced by the variables studied. From the hypothesis test, it was found that promotions and short videos have a significant influence on purchasing decisions, while live streaming does not have a significant influence. These findings provide important guidance for marketers crafting more effective digital marketing strategies on TikTok.